Getting to Know the Term of Class Size Reduction (CSR) and Its Positive Impact in The World of Education (Historical Review) - Mustofa Aji Prayitno (COMPETITIVE: Journal of Education, 2023)
Class size reduction (CSR) program is a policy that has been implemented in the world of education to improve the quality of teaching and learning. This research aims to provide a historical review of CSR and its positive impact on education. Through library research, this study collects information on the CSR concept, evaluates CSR programs that have been implemented in various countries, and analyzes the positive impacts of those programs, such as increased teacher attention, improved social interaction, higher academic achievement, better teacher job satisfaction, enhanced equity, fewer discipline problems, more time for instruction, more time for individualization, and more varied instructional learning strategy. However, there are also criticisms of CSR, such as the high cost and the lack of consistent empirical evidence regarding its impact on student academic achievement. This study concludes that CSR is a promising policy for improving the quality of education, but its implementation requires careful consideration and evaluation. The findings of this study can provide insights for policymakers and education practitioners in deciding to implement CSR in their schools.